Melatonin in Treatment of Sleep Disorders in Elderly Patients with Chronic Obstructive Pulmonary Disease - Lyubov N. Tsvetikova; Olga V. Goncharenko; Andrey V. Budnevsky; Evgeniy S. Ovsyannikov; Vladislav N. Belov; Evgenia A. Kudashova; Yanina S. Shkatova (International Journal of Biomedicine, 2017)
Background: Chronic obstructive pulmonary disease (COPD) may frequently be complicated by sleep disorders, which worse quality of life and lead to other adverse consequences. The objective of the study was to analyze clinical course of the disease and quality of life in elderly patients with both COPD and sleep disorders. Methods and Results: The study included 50 patients with moderate and severe COPD in age from 60 to 75 years (mean age, 66.12 ± 0.76 years). Patients were divided into 2 groups randomly. For patients in Group 1, 3 mg of melatonin was prescribed orally 30–40 minutes before bedtime for 14 days on the background of standard COPD therapy. Patients of Group 2 received only standard COPD therapy. After 12 months of follow-up, the number of exacerbations and hospitalizations for COPD significantly decreased in Group 1: from 3.74±0.19 to 1.91±0.20 times a year (P=0.0000) and from 2.08±0.18 to 1.35±0.18 (P=0.0046). In Group 2, the dynamics of these parameters was not statistically significant. In addition, along with the improvement of sleep quality in COPD patients during treatment with melatonin, both state and trait anxiety scores and depression level improved. In Group 1, SF-36 scores (PF, RP, BP, and GH) have also significantly improved. Conclusion: Correction of sleep disorders by melatonin in elderly patients with COPD improved the effectiveness of COPD treatment, and reduced the frequency and duration of exacerbations and the number of outpatient visits and hospitalizations.